Sedimentazione fine della Wood Bay (Mare di Ross occidentale, Antartide). - COLIZZA, ESTER; FINOCCHIARO, FURIO; IVALDI R; TOLOTTI R. (2004)
During 2001-2002 P.N.R.A. (Programma Nazionale di Ricerca in Antartide) oceanographic cruise, a first survey in a new basin discovered in the inner part of Wood Bay was performed. Sub Bottom Profiler (3.5 kHz) results have evidenced wide areas covered by transparent fine sediments. Preliminary study on two sediment cores has permitted to get some paleoenvironmental considerations about late Pleistocene-Holocene evolution of the basin